Fabrication of Randomly Stooped Polymer Nanohairs Using Scattered Electron Flood under Ambient Condition - Jung, Woojin; Jeon, Gyeong G.; Kim, Jong Uk; Kim, Tae il; Kim, Jong H. (Macromolecular Research, 2019)
Despite attractive applications of randomly oriented nanostructures with high aspect ratio, their fabrication suffers from both complicated processes and lack of materials. In this letter, we present a simple but effective method for the fabrication of randomly stooped polymeric nanohairs havinghigh aspect ratio under ambient condition by using scattered electron flood. High aspect ratio vertical nanohairs prepared by nano-molding process exhibited randomly stooped geometry after the electron irradiation. Fourier transform infrared spectroscopy and Monte Carlo simulation revealed that radiolysis of polymeric nanohairs by scattered electrons in ambient air allowed directionally random distribution of shrinkage of the nanohairs, resulting in randomly stooped nanohair structures. [Figure not available: see fulltext.].
Keywords: Ambient air; Ambient conditions; High aspect ratio; Nano molding; nanohairs; Oriented nanostructures; Random distribution; Scattered electrons; electron beam; nanohairs; nanolithography; polymer; polymer shrinkage; scattered electron